684Childhood Risk Factors and Adult Cardiovascular Disease Outcomes The International Childhood Cardiovascular Cohort (i3C) Consortium. (2nd September 2021) - Dwyer, Terence; Raitakari, Olli T.; Jacobs, David; Woo, Jessica G.; Urbina, Elaine M.; Bazzano, Lydia; Juonala, Markus; Viikari, Jorma; Chen, Wei; Prineas, Ronald; Steinberger, Julia; Daniels, Stephen; et al.
Abstract: Background: Atherosclerosis develops silently for decades before adult cardiovascular disease (aCVD) occurs. There is currently no evidence directly linking childhood risk factors to aCVD outcomes. Methods: i3C is an international consortium of 7 cohorts involving 40, 709 participants enrolled between 1970-95 in childhood (age 3-19) who underwent measurement for BMI, SBP, total cholesterol, and triglycerides, and smoking (the last mostly in adolescence). Participants were followed by direct contact and review of medical records or death registry ascertainment through adulthood in 2014-19. 20, 560 participants were found and interviewed or had died in the approximately 40 years since enrollment; 738 had a CVD event, confirmed by medical record review (n = 449) or death certificate ICD code (n = 289). Results: Estimated hazard ratios (HRs) for childhood risk factors and their confidence intervals are displayed in the table below. The CIs excluded 1.0 for all these variables in the univariable analysis and, although the HRs were reduced in multivariable analysis which included all of these risk factors, the CIs still excluded 1.0. Conclusion: Exposure to CVD risk factors in youth predicts adult CVD with implications for primordial CVD prevention. Key messages: Intervention to reduce CVD risk factors in childhood is likely to reduce risk of adult CVD